Kalimas River Tourism In Surabaya As A Culinary Tourism And Various Cultural Visitors - Nugroho, Truli; Djong, Alexander Mario Retto; Faskahariyanto, Kristian (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Kalimas River Tourism in Surabaya is one of the tourism object developments in the city of Surabaya. Tourism is a travel activity carried out by some or a group of people by visiting certain places for the purposes of recreation, personal development, or studying the uniqueness of the tourist attractions visited within a temporary period. Along the river, apart from enjoying Kalimas river tourism, visitors can also enjoy historical tourism. The historical tourism presented is a relic of the Dutch colonial era. Historical Tourism is a journey to experience places and activities that authentically depict the history and people of that time. Apart from enjoying the beauty of the Kalimas river with its inherent history. Tourists are also pampered with culinary tours at designated spots or areas. River tourism is very useful for learning the history of the city of Surabaya and efforts to increase tourist destinations in the city of Surabaya. One of the tourism icons of the city of Surabaya is the Kalimas River Tourism as a historical and culinary tourism. The research discusses river tourism as historical tourism. By looking for various scientific works and direct observations for references. So that the results obtained from following the river as a form of historical tourism.